Pelatihan Penggunaan Aplikasi Microsoft Word bagi Siswa Kelas XII Madrasah Aliyah Mambaul Ulum Paiton - Moh. Rofiki; Nur Siska Aprilia Putri; Fatimatus Zahro (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Community Service Programme at MA Mambaul Ulum Paiton focuses on improving the digital literacy of grade XII students through Microsoft Word training. This initiative addresses the urgent need for the students to acquire essential office software skills, which are critical for success in higher education and professional environments. The programme is implemented through three stages viz: planning, implementation, and monitoring and evaluation. It starts with identifying students' skill gaps, designing a phased curriculum, and delivering hands-on practice-based training. Training sessions covered basic topics, including an introduction to the Microsoft Word interface, formatting and organising documents, as well as advanced features such as creating tables and creating charts. To maximise learning outcomes, training was conducted in small groups, using interactive teaching methods and continuous evaluation. The results showed significant improvements in students' competencies, demonstrating the programme's ability to effectively bridge the digital skills gap. In addition, the initiative also provides long-term benefits by improving students' readiness to face academic and professional challenges. This effort not only fulfils an educational need, but also strengthens the overall quality of education contributing to the growth of digital literacy in MA mambaul Ulum.